INDEKS KEPUASAN MASYARAKAT DAN STANDAR OPERASIONAL PROSEDUR PROGRAM e-KTP SE-BANDAR LAMPUNG - Herlina, Herlina; Wibasuri, Anggalia (Jurnal Manajemen Magister Darmajaya, 2016)
E-KTP program is now running in Bandar Lampung, the plan passes the E-KTP program was completed until April 2012 but until now many people have not implemented E-KTP program in their respective districts. Due to the administrative services in the district less than the maximum because the equipment is broken scanner, the Internet is often "crash" for hours cause the target of one unit of computer equipment reached 108 but only 70 reached the point that the process of creation of e-ID cards and the equipment stops just one for 90,000 people and things this is the "hot" because of their work time lost while waiting in line for too long in the district. The purpose of this study was to determine the amount of public satisfaction index and determine the manufacture of standard operating procedures (SOPs) on E-KT program in each district as Bandar Lampung. Results from Tanjung Senang district to have the unit with the highest performance is Very Good with quality service and value IKM A 97.475. While Sukabumi district performing unit with the lowest predicate is Not Good with quality service and value IKM C 46.525. While the other 11 districts have a performance unit with the predicate B Good with quality of service and value that varies SMEs. While the results of SOP as a standard set of norms and allow members of the public and individuals know how the level of service expected/desired; standard focuses on the core and critical tasks that must be shown on the actual situation and in accordance with local conditions; standards improve efficiency and lead to resource utilization better power; standards improve staff utilization, staff motivation and standards can be used to assess the practical aspects of both the ground state and the post-basic education and training.Â Keyword : Community Satisfaction Index, Standard Operating Procedures, E-KTP Program